Impact of Vortioxetine on severity, cognitive dysfunctions, and functionality in patients with major depression: a real world experience from Pakistan - Minhas, Fareed Aslam; Rusham Zahra Rana; Hamdani, Syed Usman; Mowadat Hussain Rana (Journal of Pakistan Psychiatric Society, 2021)
PREVIDA stands for Pakistani study on Real world Evidence with Vortioxetine in major Depression in Asia.Anywhere in the world, a clinician’s and a patient’s real-world experience with antidepressant treatment is expected to take place minimally in the following spheres:Impact on severity of depression.Improvement in functioning at cognitive level, work performance, and productivity.Safety and tolerabilityTreatment adherenceCost of treatmentIn the PREVIDA study we have studied the performance of vortioxetine as a medication intervention in depression on all of the above spheres across Pakistan on almost 500 patients. The manufacturers provided the drug to patients free of cost over three months.